Quantitative spectrophotometric estimation of cefadroxil using hydrotropic solubilization technique - Shukla, Ravi S; Patel, Asha; Soni, M L; Modi, Vishesh; Jaliwala, Y A (Asian Journal of Pharmaceutics (AJP), 2014)
Hydrotropy is one of the reliable methods to enhance aqueous solubility of poorly soluble drugs. In the present investigation, hydrotropic solution of urea (6 M) was employed as a solubilizing agent to solubilize the poorly water- soluble drug, cefadroxil, in the tablet form and determined with the help of spectrophotometric determination in ultraviolet region. In solubility determination study, it was found that there was more than 10-fold enhancement in solubility of cefadroxil in 6-M urea solution. Cefadroxil showed maximum absorption at 263 nm and obeyed Beer’s law in concentration range of 10-80 μg/ml. Results of analysis were validated statistically and by recovery studies. The proposed method is new, simple, eco-friendly, economic, and accurate and can be utilized in routine analysis of cefadroxil tablets.